Spinozistic expression as signification. Issue 1 (2nd January 2022) - Salgado Borge, Antonio
ABSTRACT: I propose a new interpretation of Spinoza's obscure but important concept of 'expression'. Any account of Spinozistic expression must be able to fulfil two principal requirements. First, it must be able to accommodate all the relevant cases of 'to express' ( exprimire ) posited by Spinoza in the Ethics . Second, it must be able to deal with the fact that for Spinoza all instances of 'to express' are instances of 'to involve' ( involvere ). By taking both 'to express' and 'to involve' as coextensive with 'to conceive', contemporary accounts of Spinozistic expression satisfy the latter requirement, but they fail to satisfy the former. In this article, I dispute the claim that for Spinoza 'to express' is coextensive with 'to conceive'. I argue instead that Spinoza understands exprimire as natural signification: for Spinoza, 'to express' is coextensive with 'to be a natural sign of'. I show that this interpretation is not only able to successfully deal with both requirements of Spinozistic expression, but also offers a novel and textually supported insight to Spinoza's understanding and use of the elusive concept of 'expression'.